2015
DOI: 10.1104/pp.15.01040
|View full text |Cite
|
Sign up to set email alerts
|

BnaC9.SMG7b functions as a positive regulator of number of seeds per silique in rapeseed (Brassica napus L.) by regulating the formation of functional female gametophytes

Abstract: Number of seeds per silique (NSS) is an important determinant of seed yield potential in Brassicaceae crops, and it is controlled by naturally occurring quantitative trait loci. We previously mapped a major quantitative trait locus, qSS.C9, on the C9 chromosome that controls NSS in Brassica napus. To gain a better understanding of how qSS.C9 controls NSS in B. napus, we isolated this locus through a map-based cloning strategy. qSS.C9 encodes a predicted small protein with 119 amino acids, designated as BnaC9.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 70 publications
2
58
1
Order By: Relevance
“…It should be noted that the numbers of ovules per ovary were significantly larger than the corresponding numbers of seeds per pod for all of the nine lines ( Figures 1B, 6 ), in accordance with the previous studies (Li et al, 2014; Li, 2015). This suggested that the number of ovules/seeds per ovary/pod should decrease from flowering to maturity.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It should be noted that the numbers of ovules per ovary were significantly larger than the corresponding numbers of seeds per pod for all of the nine lines ( Figures 1B, 6 ), in accordance with the previous studies (Li et al, 2014; Li, 2015). This suggested that the number of ovules/seeds per ovary/pod should decrease from flowering to maturity.…”
Section: Resultssupporting
confidence: 92%
“…It should be noted that the number of seeds per pod for the elite cultivar Zhongshuang11 is much more less than the number of ovules per ovary as well as its maximum reported in the current ( Figure 6 ) and previous (Li et al, 2014; Li, 2015) studies. In addition, both the fertilization rate of ovules and the survival rate of fertilized ovules for the elite cultivar Zhongshuang11 were less than the maximum observed in the current studies ( Figure 8 ).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The overexpression of BcRISP1 in Arabidopsis showed reduced seed set and short siliques, which is caused by the reduced pollen formation and impaired pollen tube elongation due to the interruption of the mitochondrial electron transport chain by affecting the expression of mitochondrial breathing chain‐related genes (Liu et al , ). A major QTL qSS.C9 for seeds per silique has been cloned on the C9 chromosome of Brassica napus (Li et al , ), which encodes a predicted small protein with 119 amino acids homologous to the Arabidopsis SMG7 gene that is involved in meiotic cell cycle. The BnaC9.SMG7b was mainly expressed in the vascular tissue of various organs, including cotyledons, rosette leaves, roots, young pedicels and pistils, but not in stamens, petals, stems and mature siliques.…”
Section: Other Proteinsmentioning
confidence: 99%
“…The stained samples were mounted in 30% glycerol and observed under an Axio Scope A1 fluorescence microscope (Carl Zeiss) with a UV filter. Observation for callose deposition in the meiotic megasporocytes and megaspores was as described (Li et al, 2015).…”
Section: Anther Cross-sectioning and Callose Detectionmentioning
confidence: 99%